Convergent studies on Pleurotus ostreatus spent mushroom substrate compost as a sustainable heavy metal biosorbent / Tay Chia Chay - Tay, Chia Chay (2012)
Pleurotus ostreatus spent mushroom substrate compost (PSMC) is an agricultural waste from mushroom cultivation farms. The potential of PSMC as biosorbent for heavy metal biosorption in batch mode was explored in this study. The optimization and evaluation of washing pretreatment in biosorbent preparation, advanced characterisation of biosorbent, optimization of biosorption, evaluation of existing models, application of biosorbent and Artificial Neural Network (ANN) modeling were investigated. Parameters of 20 g/L biosorbent concentration, two hours immersion time and three cycles of washing pre-treatment were determined as the optimized washing pretreatment conditions in biosorbent preparation. Besides effectively remove contaminants, this new approach not only increased heavy metal biosorption efficiency but also exhibited good repeatability and reproducibility for Ni(II) biosorption efficiency and different batches biosorbent respectively. Results from advanced characterization indicated that PSMC biosorbent has surface area of 5.5544 x 10-1 m2/g. The basic component of PSMC is lignocelluloses while minor components are chitin and protein. Carboxyl, hydroxyl and amide functional groups of these components were involved in the heavy metal biosorption process. Heavy metal biosorption process is complex and involved several simultaneous mechanisms including ion exchange, chemisorptions and complexation. An adopted approach using the experimental design of TORCHIA 13C ssNMR was applied in biosorbent advanced characterisation analysis. It has ascertained that complexation occurred through lignin-Pb(II) complexes. In order to shorten the time to obtain reliable results and reduced the usage of biosorbent, another adopted approach using half saturation constant concentration was established for optimization of heavy metal biosorption. The half saturation constant biosorbent was found to be at 0.08 g for Pb(II) and 0.7 g for both Cu(II) and Ni(II). In single, bi- and multi-heavy metal iii biosorption, the selectivity of biosorbent followed the order of Pb(II), Ni(II) and finally Cu(II). This observation corresponded to the descending order of heavy metal electronegativity. Experimental data are well fitted to Langmuir isotherm, pseudo second-order kinetic and thermodynamic models (r2 > 0.88). These data fittings indicate that heavy metal biosorption is a monolayer, not uni-molecular and spontaneous exothermic reaction. Chemisorptions act as rate limiting step in heavy metal biosorption. For application of biosorbent in treatment of automobile wastewater containing Ni(II), a lower biosorption efficiency was observed when compared to single heavy metal solution due to competition of cations and protons for the similar binding sites. In addition, the experiments were not operated under optimised conditions. For heavy metals recovery study, a high recovery of heavy metal from biosorbent about 90 % was achieved by using dilute 0.1M nitric acid to minimize secondary waste products. While for the predictive modeling, a multiple input and multiple output ANN model which is a novel approach has been successfully introduced for biosorption modeling. This ANN model, with excellent sensitivity analysis, is not only useful in plant operational management but also for prediction of effluent quality. It is suggested that PSMC has high potential to be developed as biosorbent. The good biosorption performance and high recovery of heavy metals from biosorbent contribute to a low impact, environmental friendly sustainable remediation technology. In addition, such characteristics also make it favorable for larger scale wastewater purification application that is based on continuous operation in a fixed-bed column.